Multi-scale-phases coherent precipitation improve the comprehensive performance of heat-resistant Cu alloys - Y.L. Hu; M. Li; Y.D. Hou; X.N. Li; Z.M. Li; Z.L. Cheng; Y.Y. Shao; Y.H. Zheng; C. Dong (Journal of Materials Research and Technology, 2023)
High-temperature destabilization of the strengthening phase and the generation of discontinuous precipitation at grain boundaries are mutual problem in current high-temperature alloys, especially in the novel Cu-based high-temperature alloys. In the present work, multicomponent composition design is utilized to inhibit discontinuous precipitation and improve the stability of the γ′ phase by strong enthalpic interactions between elements, while introducing coherent precipitated phases other than the γ′ phase into the alloy to simultaneously enhance the heat resistance of the alloy. The Cu85.71Ni10.72-xAl3.57Mx (M = Ti, Nb and V) alloys designed are multi-scale-phases coherent precipitation-strengthened copper alloys, as shown by systematic electron diffraction and HRTEM analysis. In-situ analysis of high temperature hardness and electrical resistivity showed that the softening rate of hardness and the rising rate of electrical resistivity decreased significantly after adding M during the heating process. The calculation results by Thermo-calc also confirmed that the addition of M delayed the re-dissolution of the γ′ phase to improve its thermal stability, and introduced additional coherent precipitated phases which remains a strengthening effect after the re-dissolution of the γ′ phase at high temperature. The enhanced stability of γ′ phase originates from the strong enthalpic interaction between elements and is also related to the promotion of precipitation of Al and reduction of vacancies and antisites in γ′ phase by adding M. In summary, multi-scale-phases coherent precipitation strengthening is an effective way to enhance the comprehensive performance of novel Cu-based high-temperature alloys, and also provides a new perspective for the development of heat-resistant alloys with excellent performance.